Penyuluhan Pengelolaan Sampah dengan Konsep 3R dalam Mengurangi Limbah Rumah Tangga - Trisnawati Oky Ristya (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2020)
Garbage is one of the problems that is quite difficult to handle in Indonesia. The existence of household waste (garbage) generated as a result of human activities has many impacts on humans and the surrounding environment. There is still a lot of organic and inorganic waste produced by community activities in the environment around the settlements of Kebadongan Village residents originating from household activities. Implementation of counseling and provision of training waste management and utilization using the 3R concept (Reduce, Reuse, Recycle) or reducing, reusing and recycling waste is an effective way to be able to create an area with an independent level of waste management that will help the government to create healthy, clean and comfortable environment. This research was conducted with the aim of: (1) providing knowledge to the community about the importance of sorting organic and inorganic waste as the initial key to implementing the 3R concept and (2) providing knowledge to the community in processing organic waste into compost and processing inorganic waste into various types of crafts. hand. This research activity was carried out in Kebadongan Village on Sunday 20 January 2019 at 11.00 in the village hall using lecture, demonstration and discussion methods. Implementation of research activities can be described through 3 (three) stages of activity, namely preparation, implementation and evaluation. The real results obtained from the education and waste management training activities using the 3R concept are increasing public knowledge about waste. The community is also aware of and starting to get used to sorting organic and inorganic waste as the initial key to implementing the 3R concept. The use of the 3R concept (reuse, reduce, recycle) can inspire residents to create an area with an independent level of waste management that will help the government to create a healthy, clean and comfortable environment. In addition, public knowledge about organic and inorganic waste management is also increasing.